Complexity of downy birch emissions revealed by Vocus proton transfer reaction time-of-flight mass spectrometer - Thomas, Steven Job; Li, Haiyan; Praplan, Arnaud P.; Hellén, Heidi; Bianchi, Federico (Frontiers in Forests and Global Change, 2022)
Biogenic volatile organic compounds (BVOCs) are known to strongly influence the global climate by affecting various atmospheric constituents such as oxidants and aerosols. Among the several BVOCs that are emitted continuously into the atmosphere, studies have shown that up to 96% of the emissions have been missed out by current analytical techniques. In this study, we used a Vocus proton-transfer-reaction time-of-flight mass spectrometer (Vocus) to characterise and quantify emissions from a branch of a downy birch tree at a boreal forest site in Hyytiälä, Finland in August 2019. During the measurement period, we were able to observe real-time emissions of hydrocarbons with up to 20 carbon atoms and oxygenated compounds (OVOCs) with up to 4 oxygen atoms. OVOCs accounted for around 90% of the total observed emissions with the largest contribution from C8H8O3 (0.37 µgg-1h-1; 60% of total). For the first time, emissions of diterpenes (C20H32, C20H36, and C20H38) were observed from downy birch tree, although in minor quantities (0.1% of total emissions). During this late growing season, C10H16 and C10H14 contributed 7% in total emissions, while the sum of C5H8, C15H22, and C15H24 contributed around 3%. The branch experienced abiotic stress during the measurement period, which might explain the unusually high emissions of C8H8O3. Standardized emission potentials are reported for all compounds using the Guenther algorithms. While emissions of most compounds fit well with either of the two algorithms, emissions of certain compounds like C8H8O3 could not be explained by either suggesting the influence of other factors besides temperature and light. Vocus PTR-TOF-MS can help identify a diverse range of molecules even if emitted in minute quantities. The BVOCs detected from birch emissions may be important in the formation of secondary organic aerosols but their implications in the atmosphere need to be verified with further studies.